Building the evidence on Making Health a Shared Value: Insights and considerations for research - May Lynn Tan; David Vlahov; Erin Hagan; M. Maria Glymour; Laura M. Gottlieb; Ellicott C. Matthay; Nancy E. Adler (Elsevier, 2019)
The Robert Wood Johnson Foundation (RWJF)'s Culture of Health Action Framework guides a movement to improve health and advance health equity across the nation. Action Area One of the Framework, Making Health a Shared Value, highlights the role of individual and community factors in achieving a societal commitment to health and health equity, centered around three drivers: Mindset and Expectations, Sense of Community, and Civic Engagement. To stimulate research about how Action Area One and its drivers may impact health, Evidence for Action (E4A), a signature research funding program of RWJF, developed and released a national Call for Proposals (CFP). The process of formulating the CFP and reviewing proposals surfaced important challenges for research on creating and sustaining shared values to foster and maintain a Culture of Health. In this essay, we describe these considerations and provide examples from funded projects regarding how challenges can be addressed. Keywords: Culture of health, Mindset and expectations, Civic engagement, Sense of community, Shared values, Health equity